Health Design Thinking: An Innovative Approach in Public Health to Defining Problems and Finding Solutions - Abookire, Sylvie; Plover, Colin; Frasso, Rosemary; Ku, Bon (Frontiers in Public Health, 2020)
Current trends in the United States health care landscape call for innovative and adaptive approaches to improve outcomes and reduce inefficiencies. Design Thinking is an innovative approach to problem-solving that leverages insights from the end-users of new products, services and experiences in order to develop best-fit solutions that are rapidly prototyped and iteratively refined. When compared to traditional problem-solving methods in healthcare and other public health adjacent fields, Design Thinking leads to more successful and sustainable interventions. Design Thinking has facilitated improvements in patient, provider, and community satisfaction, and in public health, has increased efficiency and collaboration in intervention development. Given the promising nature of Design Thinking as an effective problem-solving method, it follows that Design Thinking training would prove a beneficial addition to public health education. The integration of Design Thinking in public health education may equip public health leaders with essential skills necessary to understand and more effectively approach historically intractable challenges. This article describes the development and evaluation of a hands-on Design Thinking workshop, piloted with Master of Public Health (MPH) students in April, 2019 at Thomas Jefferson University. Preceding and following the workshop, evaluation forms were used to assess participants' knowledge about Design Thinking concepts and attitudes towards the workshop experience. Metrics aligned with established learning objectives relating to process, impact, and outcomes. We hypothesized that the workshop intervention would increase participants understanding of Design Thinking concepts and applications in public health. Evaluations demonstrated that after attending the workshop, participants were able to understand and apply Design Thinking concepts in a public health context. Following the evaluation of pilot data, the workshop was refined and embedded in the MPH curriculum at Thomas Jefferson University in Philadelphia, PA.